Butyrolactone-I from Marine Fungal Metabolites Mitigates Heat-Stress-Induced Apoptosis in IPEC-J2 Cells and Mice Through the ROS/PERK/CHOP Signaling Pathway - Xueting Niu; Shengwei Chen; Xinchen Wang; Jiaying Wen; Xiaoxi Liu; Yanhong Yong; Zhichao Yu; Xingbing Ma; A. M. Abd El-Aty; Xianghong Ju (Marine Drugs)
Heat stress poses a significant challenge to animal husbandry, contributing to oxidative stress, intestinal mucosal injury, and apoptosis, which severely impact animal health, growth, and production efficiency. The development of safe, sustainable, and naturally derived solutions to mitigate these effects is critical for advancing sustainable agricultural practices. Butyrolactone-I (BTL-I), a bioactive compound derived from deep-sea fungi (Aspergillus), shows promise as a functional feed additive to combat heat stress in animals. This study explored the protective effects of BTL-I against heat-stress-induced oxidative stress and apoptosis in IPEC-J2 cells and mice. Our findings demonstrated that BTL-I effectively inhibited the heat-stress-induced upregulation of HSP70 and HSP90, alleviating intestinal heat stress. Both in vitro and in vivo experiments revealed that heat stress increased intestinal cell apoptosis, with a significant upregulation of Bax/Bcl-2 expression, while BTL-I pretreatment significantly reduced apoptosis-related protein levels, showcasing its protective effects. Furthermore, BTL-I suppressed oxidative stress markers (ROS and MDA) while enhancing antioxidant activity (SOD levels). BTL-I also reduced the expression of p-PERK, p-eIF2α, ATF4, and CHOP, mitigating oxidative and endoplasmic reticulum stress in intestinal cells. In conclusion, BTL-I demonstrates the potential to improve animal resilience to heat stress, supporting sustainable livestock production systems. Its application as a natural, eco-friendly feed additive will contribute to the development of sustainable agricultural practices.